CONSEQUENCES OF NEPALESE YOUTH MIGRATION TO OVERSEAS FOR FOREIGN EMPLOYMENT - Pankaj Das (Jurusan Sosiologi FISIP UNIB, 2020)
Nepal is an agricultural country, where migration is increasing for foreign employment. Majority of workers from Asia mostly from Nepal migrate to Middle East countries. Migrant workers working in these countries suffer from work related risk like accidents at workplace and mental sickness. Foreign migration has shifted the agricultural economy towards remittance economy. Lack of education and limited employment opportunities are the main reasons behind international labor migration. The issue of such migration needs to be addressed at the government level, to assist in managing and promoting safe migration in an effective way.Keywords: Foreign Employment, Health risks. Migration